Infant and young child feeding practices among mothers attending an Urban Health Training Centre (UHTC): a cross-sectional (mixed methodology) study in Berhampur, South Odisha, India - Karmee, Nivedita; Satapathy, Sushree Priyadarsini; Tripathy, Radha Madhav (International Journal of Contemporary Pediatrics, 2017)
Background: Adequate nutrition during infancy and early childhood is essential to ensure the health, growth and development of children. The objective of this study was to assess infant and young child feeding practice among mothers with 0-24 months children as per WHO criteria. Methods: It was a cross sectional study, involving mixed methodology (quantitative method supplemented by qualitative method in-depth interview) among 374 respondents from 1st May 2017 to 31st August 2017. Results: In quantitative method: 49 (81.6%) reported to have started breast feeding within first hour after delivery. 47 (78.3%) respondents exclusively breast fed their infants. In qualitative method: 69.78% mother were of age group 18-29 years. 52.14% respondents were educated up to primary/middle school. In multiple logistic regression analysis educational status of mother, occupational status of mother, birth place, ANC follow up, EBF education at ANC, type of delivery was found to be significant. Conclusions: IYCF practice was poor. Therefore, there is a need for emphasizing upon the promotion of IYCF practice by health care providers.